2019
DOI: 10.3389/fimmu.2019.01005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mannose Binding Lectin Gene Variants in Pediatric Influenza Virus-Related Critical Illness

Abstract: Background: Mannose-binding lectin (MBL) is an innate immune protein with strong biologic plausibility for protecting against influenza virus-related sepsis and bacterial co-infection. In an autopsy cohort of 105 influenza-infected young people, carriage of the deleterious MBL gene MBL2 _Gly54Asp(“B”) mutation was identified in 5 of 8 individuals that died from influenza-methicillin-resistant Staphylococcus aureus (MRSA) co-infection. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…ARDS pathobiology is characterized by inflammation, loss of the alveolar epithelial, and lung vascular endothelial permeability barriers, dysregulated coagulation, and fibrosis. Recent advances related to individual and combinations of plasma biomarkers indicative of many of these aspects of PARDS pathobiology and studies aimed at identifying subphenotypes at greater risk of worse clinical outcome and/or response to therapy are described in the sections below (5, 22, 45, 49, 70, 96–139). Subphenotype identification offers enhanced prognostic ability beyond what bedside physiologic biomarkers and/or PARDS trigger (e.g., pneumonia, sepsis, trauma, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ARDS pathobiology is characterized by inflammation, loss of the alveolar epithelial, and lung vascular endothelial permeability barriers, dysregulated coagulation, and fibrosis. Recent advances related to individual and combinations of plasma biomarkers indicative of many of these aspects of PARDS pathobiology and studies aimed at identifying subphenotypes at greater risk of worse clinical outcome and/or response to therapy are described in the sections below (5, 22, 45, 49, 70, 96–139). Subphenotype identification offers enhanced prognostic ability beyond what bedside physiologic biomarkers and/or PARDS trigger (e.g., pneumonia, sepsis, trauma, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, interpretation of genetic association studies for PARDS must be considered with this limitation in mind. In the last 10 years, studies have shown no association of specific variants in IL-1 receptor antagonist (116), IL-8 (119), caspase-12 (97), mannose-binding lectin (98), and interferon-induced transmembrane protein 3 (49) with PARDS. A study of children with pneumonia suggests that polymorphisms in the splicing factor CUGBP, Elav-like family member 2 that regulates splicing of cystic fibrosis transmembrane conductance regulator may be associated with increased risk for PARDS (100).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown MBL’s protection also in vivo and it has been suggested that MBL deficiency may be a risk factor for influenza A virus infection (Chang et al 2010 ). Nevertheless, in a recent report where 420 patients with confirmed influenza-critical illness were studied, MBL deficiency was not found to be a risk factor for very severe influenza infection in children and adolescents (Levy et al 2019 ) (Table 1 ).…”
Section: Mbl Associated With Diseasesmentioning
confidence: 99%
“…Children (<2 years) with MBL deficiency are in higher risk for PM Bautista-Rodriguez et al ( 2017 ) Bacterial infection Pneumonococcal infection MBL does not drive lectin pathway activation on the surface of S. pneumoniae Ali et al ( 2012 ) Respiratory Tract Infection Pneumonococcal disease Low MBL production could be associated with IPD in children <2 years Muñoz-Almagro et al ( 2014 ) Viral infection Influenza A viral infection In vivo studies on mice about protection of MBL from IAV infection. Suggesting MBL deficiency as a risk factor for IAV infection Chang et al ( 2010 ) Viral infection Influenza virus-related critical illness MBL deficiency is not a risk factor for severe influenza infection in children and young adults Levy et al ( 2019 ) Viral infection HIV There is an association between undetectable serum MBL concentrations and susceptibility to HIV infection. But the course of HIV infection does not seem to be influenced by the level of MBL Nielsen et al ( 1995 ) Viral infection HIV Homozygous carriers of MBL alleles are at increased risk of HIV infection Garred et al ( 1997 ) Autoimmune diseases Systemic lupus erythematosus Increased frequency of MBL allele (codon 54) in patients with SLE, but it represents a minor risk factor for this disease.…”
Section: Mbl Associated With Diseasesmentioning
confidence: 99%
See 1 more Smart Citation